A Hit? or A Miss? Learning From Errors: A Misplaced Nasogastric Tube - Sinha, Ansha; Gothi, Dipthi; Soni, Deep Kamal; Kumar, Sunil (Asian Pacific Journal of Cancer Care, 2025)
A 76-year-old poorly built female presented to the emergency department with right sided acute chest pain and breathlessness after an episode of unprovoked heavily strained vomiting, consisting of food particles and blood streaks. Chest radiograph showed right sided hydro-pneumothorax. Intercostal drain insertion was done immediately, and her symptoms improved. Patient’s son noticed rice particles in the ICD bag after she had consumed it for lunch that day. A nasogastric tube insertion was done. The chest radiograph obtained after the insertion showed a peculiar course. The tube did not reach its designated goal, but it helped in diagnosis of occult esophageal carcinoma.